Phytochemical Analysis, In Silico Drug-likeness, and ADMET Profiling of Bioactive Compounds from Methanolic Extract of Ixora coccinea Using GC-MS: Research Article (Journal of Pharma Insights and Research, 2025)
A systematic investigation of methanolic extracts from Ixora coccinea leaves, stems, and flowers was conducted to evaluate their pharmaceutical potential. Soxhlet extraction yielded a complex mixture of phytoconstituents, which underwent detailed phytochemical screening confirming the presence of alkaloids, steroids, flavonoids, terpenoids, and glycosides. GC-MS analysis revealed 86 distinct bioactive compounds, with retention times ranging from 7 to 37 minutes. The molecular structures and physicochemical properties of identified compounds were validated using PubChem database. Drug-likeness evaluation based on Lipinski's Rule of Five parameters indicated favorable oral bioavailability for most compounds. ADMET profiling through PKCSM web server predicted high intestinal absorption (>90%) for major constituents, selective blood-brain barrier permeability, and minimal hepatotoxicity risks. Notable compounds including 1,5-dimethylpyrazole, 5-hydroxymethylfurfural, and cyclobutane derivatives exhibited optimal pharmacokinetic profiles. The identified compounds showed variable metabolic patterns, with specific interactions with CYP3A4 and CYP1A2 enzymes. Toxicological assessment indicated low mutagenicity and cardiotoxicity risks for most compounds, though some exhibited positive AMES test results. The results indicate a hopeful opportunity for developing novel therapeutic agents from I. coccinea, warranting further in vivo investigations